Soil organic carbon and clay content as deciding factors for net nitrogen mineralization and cereal yields in boreal mineral soils. (1st July 2020) - Soinne, Helena; Keskinen, Riikka; Räty, Mari; Kanerva, Sanna; Turtola, Eila; Kaseva, Janne; Nuutinen, Visa; Simojoki, Asko; Salo, Tapio
Abstract: To achieve appropriate yield levels, inherent nitrogen (N) supply and biological N fixation are often complemented by fertilization. To avoid economic losses and negative environmental impacts due to over‐application of N fertilizer, estimation of the inherent N supply is critical. We aimed to identify the roles of soil texture and organic matter in N mineralization and yield levels attained in cereal cultivation with or without N fertilization in boreal mineral soils. First, the net N mineralization and soil respiration were measured by laboratory incubation with soil samples varying in clay and organic carbon (C) contents. Secondly, to estimate the inherent soil N supply under field conditions, both unfertilized and fertilized cereal yields were measured in fields on clay soils (clay 30–78%) and coarse‐textured soils (clay 0–28%). In clay soils (C 2.5–9.0%), both the net N mineralization and the cereal yields (without and with fertilization) decreased with increasing clay/C ratio. Moreover, in soils with high clay/C ratio, the agronomic N use efficiency (additional yield per kg of fertilizer N) varied considerably, indicating the presence of growth limitations other than N. In coarse‐textured soils, the yield increase attained by fertilization increased with increasing organic C. Our results indicate that for clay soils in a cool and humid climate, the higher the clay content, the more organic C is needed to produce reasonable yields and to ensure efficient use of added nutrients without high N losses to the environment. For coarse soils having a rather high mean organic C of 2.3%, the organic C appeared to improve agronomic N use efficiency. For farmers, simple indicators such as the clay/C ratio or the use of non‐N‐fertilized control plots may be useful for site‐specific adjustment of the rates of N fertilization. Highlights: We aimed to identify simple indicators of inherent soil N supply applicable at the farm level. In clay soils, the net N mineralization was found to correlate negatively with the clay/C ratio. In coarse‐textured soils, agronomic N use efficiency improved with increasing soil organic C. Clay soils with high clay/C ratio are at risk of low yield levels.